Fiscal devaluations - Emmanuel Farhi; Gita Gopinath; Oleg Itskhoki (Federal Reserve Bank of Boston, 2012)
The authors show that even when the exchange rate cannot be devalued, a small set of conventional fiscal policy instruments can robustly replicate the real allocations attained under a nominal exchange rate devaluation in a standard New Keynesian open economy environment. They perform the analysis under alternative pricing assumptions-producer or local currency pricing along with nominal wage stickiness, under alternative asset market structures, and for anticipated and unanticipated devaluations. There are two types of fiscal policies equivalent to an exchange rate devaluation: one, a uniform increase in the import tariff and export subsidy, and two, an increase in the value-added tax and a uniform reduction in the payroll tax. When the devaluations are anticipated, these policies need to be supplemented with a reduction in the consumption tax and an increase in income taxes. These policies have zero impact on fiscal revenues. In certain cases equivalence requires in addition a partial default on foreign bondholders. They discuss the issues regarding implementation of these policies, in particular in the case of a currency union.
Keywords: E32; E60; F30; 330